IBM Kelompok Ibu-Ibu PKK dan Pemuda Putus Sekolah - Mujiati; Nurjaya, Hasma (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
Program of science and technology for community (IbM) entitle “IbM Family Walfare Programme (FWP) and school drop-outs” in Kendari have been conducted in subdistrict of Anduonohu Southeast Sulawesi by cooperation with two partners of women association PKK Harapan group and Pemuda Sukses. This purpose of this programme is to provide training and counselings as well as to established enterpreneurship sense in community. The result of this programme is to provide commpetency skills in bread production with good taste and texture in order to encrease selling cost.